Impact of Workforce Diversity on the Organizational Performance of Banking Sector of Nepal: A Mediating role of Managerial Expertise - Pandey , Dhruba Lal; Risal, Nischal (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
Work force diversity has become an organizational imperative and as such, it is important for organizations to understand, embrace and manage diversity to be able to outperform competitors. Researchers have produced mixed result on the impact of diversity on performance. Some scholars found a positive relation between diversity factors and performance whilst others have found negative relations between diversity factors and performance. This paper therefore examines the effect of work force diversity factors (generational diversity, gender diversity, ethnic/racial diversity) and the role of managerial expertise on organizational performance. This study followed the correlational research design as it intends to evaluate the impact of workforce diversity on banking sector performance. The population of the study was managerial level employees working in banking sector of Nepal and 156 responses were collected and analyzed. Five-point Likert scale questionnaire was used to collect the data. Correlation matrix and regression model were used to analyses the data. Physical diversity characters; age, gender and ethnicity were considered for the study. Research concluded that gender and ethnic diversity positively affect the organizational performance but age diversity may cause conflict in the organization, however, managerial expertise positively affect organization performance which can contribute to reduce conflict that arise because of age diversity in the organization.